STUDI EVALUASI DAN KEBUTUHAN FASILITAS PENYEBERANGAN DI KOTA PONTIANAK (STUDI KASUS JL. VETERAN, JL. PAHLAWAN DAN JL. SULTAN HAMID) - Hendri, Yulius; AS, Syafaruddin; Juniardi, Ferry (Jurnal Mahasiswa Teknik Sipil Universitas Tanjungpura, 2018)
The case study is located at the Veteran road crossing, namely at the crossing facility (zebra crossing), Pahlawan road and Sultan Hamid crossroad on the crossing facility (zebra crossing). Observations made related to the type of crossing facility needs at the location of the study. By evaluating existing facilities and analyzing existing or non-existing facilities for pedestrian numbers and vehicle volumes. Data collected in the form of pedestrian volume data, vehicle volume, vehicle speed data and other supporting data. The method used in the study of determining the type of crossing facility needs is the appropriate approach methods, namely determining the type of crossing facilities in accordance with the Procedure for Determining Pedestrian Facilities in Urban Areas (1995) and the Department of Advice Note TA / 10/80, while for determining the average speed of the vehicle according to the Indonesian Road Capacity Manual. In addition, it will also be seen the user's perception of the existence of zebra cross seen from function, safety, comfort, cleanliness and beauty. The evaluation results at the eight existing crossing points (zebra crossing) indicate that zebra crossing is in accordance with the provisions of pedestrian criteria, only at ZONE A, ZONE B, ZONE C, and ZONE D almost 85% of respondents think on location This requires special attention and care from the related institution. Whereas on the ZONE I of the Heroes road, which determines the type of quisioner crossing facility planned for distribution to the respondents, almost 85% of respondents want an additional crossing facility in this location. Technically, analysis of crossing facilities services is analyzed that this location (Jl. Pahlawan) is a pelican with waiting stalls, but in the analysis of interview surveys shows that the need for pedestrian facilities (respondents) is a pedestrian bridge (JPO). All study sites use zebra ross which up to now still have service levels A. The selection of planning crossing facilities at the study location (Jl.Pahlawan) is reasonable when viewed from the road width of 8-10 m per track with a high median, the speed of the vehicle is stretched which ranges from 10-18 km / h and the number of pedestrians crossing carelessly without using existing facilities (zebra crossing), so it is dangerous if there are no additional crossing facilities in the form of JPO. For the volume of vehicles at this location, which is in the north direction, it has a peak hour at 16.00-17.00 with a total of 1462.1 on Mondays and the volume of vehicles in the south direction has a peak hour at 10.00-11.00 with a total of 1394.7 pcu / hour on Friday. Determination of the type of crossing facility on the road of the hero has a degree of saturation of 0.87 in LOS D which is approaching the unstable current and low speed.Keywords: Zebra Cross, Pendestrian, JPO, Traffic flow